Emerging critical technologies and security in the Asia-Pacific - Bitzinger, Richard (Palgrave Macmillan, 2016)
The proliferation of advanced militarily relevant technologies in the Asia-Pacific over the past few decades has been a significant, and perhaps even alarming, development. This volume addresses how such technologies may affect military capabilities and military advantage in the region.